Mammalian Nudix proteins cleave nucleotide metabolite caps on RNAs. Issue 12 (20th May 2020) - Sharma, Sunny; Grudzien-Nogalska, Ewa; Hamilton, Keith; Jiao, Xinfu; Yang, Jun; Tong, Liang; Kiledjian, Megerditch
Abstract: We recently reported the presence of nicotinamide adenine dinucleotide (NAD)-capped RNAs in mammalian cells and a role for DXO and the Nudix hydrolase Nudt12 in decapping NAD-capped RNAs (deNADding) in cells. Analysis of 5′caps has revealed that in addition to NAD, mammalian RNAs also contain other metabolite caps including flavin adenine dinucleotide (FAD) and dephosphoCoA (dpCoA). In the present study we systematically screened all mammalian Nudix proteins for their potential deNADing, FAD cap decapping (deFADding) and dpCoA cap decapping (deCoAping) activity. We demonstrate that Nudt16 is a novel deNADding enzyme in mammalian cells. Additionally, we identified seven Nudix proteins—Nudt2, Nudt7, Nudt8, Nudt12, Nudt15, Nudt16 and Nudt19, to possess deCoAping activity in vitro . Moreover, our screening revealed that both mammalian Nudt2 and Nudt16 hydrolyze FAD-capped RNAs in vitro with Nudt16 regulating levels of FAD-capped RNAs in cells. All decapping activities identified hydrolyze the metabolite cap substrate within the diphosphate linkage. Crystal structure of human Nudt16 in complex with FAD at 2.7 Å resolution provide molecular insights into the binding and metal-coordinated hydrolysis of FAD by Nudt16. In summary, our study identifies novel cellular deNADding and deFADding enzymes and establishes a foundation for the selective functionality of the Nudix decapping enzymes on non-canonical metabolite caps.